Role of intravesical granulocyte-macrophage colony-stimulating factor in controlling hemorrhagic cystitis in patients undergoing stem cell transplantation - A retrospective cohort study - Akanksha Garg; Roshni Dasgupta; Sandip Shah; Kinnari Patel; Kamlesh Shah (Indian Journal of Transplantation, 2021)
Introduction: Hemorrhagic cystitis (HC) is a well-known complication in patients undergoing hematopoeitic stem cell transplantation (HSCT), contributing considerably to morbidity and prolonged hospital stay. Granulocyte-macrophage colony-stimulating factor (GM-CSF) affects the proliferation and differentiation of hematopoietic stem/progenitor cells and the functioning of monocytes, granulocytes, lymphocytes, and endothelial cells. The objective of this study was to evaluate the efficacy and safety of GM-CSF bladder irrigation for HC post-HSCT. Materials and Methods: We conducted a retrospective cohort study to assess the clinical effects of GM-CSF (GM-CSF group) in controlling HC in patients who had undergone HSCT at our institute. We also compared these patients with those who did not receive GM-CSF. Results: There were 12 patients in the GM-CSF group and seven patients in the non-GM-CSF (control) group. The median ages were 16 years (range: 4–33 years) and 19 years (range; 6–41 years), respectively. Median time-to-resolution of HC from day of onset was 9.5 days in the GM-CSF group versus 59 days in the non GM-CSF group (P = 0.001). Mortality was 85% in the control group as compared to 16% in GM-CSF group (P = 0.008). Among the GM-CSF responders, complete response was seen in eight patients (67%). None of the patients developed any systemic or local side effects to GM-CSF. Overall survival in the two groups was 75% and 14%, respectively (P = 0.043). Conclusion: GM-CSF was shown to be effective in controlling HC in post-HSCT patients, without any major side effects, along with decreased mortality and improved overall survival.